Public Sentiment Analysis on the Digital Innovation JKN Mobile as a Solution for BPJS Health Services - Yuliansyah, Romi Ali; Mandanti, Desti; Al Rizki, Muhammad Fadel; Tasya, Saskiya Reni (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2025)
This study aims to analyze public sentiment toward the JKN Mobile application to understand user perceptions regarding the speed and convenience of BPJS Health services. A total of 4,518 user reviews from the Play Store, App Store, and the X platform were collected and processed using a text analysis approach that included data cleaning, tokenization, sentiment labeling, and accuracy checking to ensure consistency. Although the number of reviews varied across platforms, which may create representation bias, this factor was considered when interpreting the findings. The results show that negative sentiment dominates more than 70 percent of all reviews. Most complaints relate to technical problems such as login failures, OTP code errors, slow application response, and system instability during busy periods, while some positive comments highlight the benefits of online registration, digital queue retrieval, and easy access to membership information. The dominance of negative sentiment not only reflects technical issues but also indicates user interaction dynamics that require further investigation to generate deeper and more unique insights. These findings have important implications for service improvement and policy development, particularly the need to strengthen server capacity, enhance authentication reliability, and establish continuous technical monitoring procedures. For policymakers, the study underscores the importance of setting measurable performance standards to ensure the reliability and effectiveness of digital health services delivered through the application in Indonesia.